American poison : a deadly invention and the woman who battled for environmental justice - Stone, Daniel (Daniel Evan), 1985- ([New York] : Dutton, 2025)
"From the national bestselling author of The Food Explorer comes the untold story of Alice Hamilton, a trailblazing doctor and public health activist who took on the booming auto industry-and the deadly invention of leaded gasoline, which would poison millions of people across America. At noon on October 27, 1924, a factory worker was admitted to a hospital in New York City, suffering from hallucinations and convulsions. Before breakfast the next day, he was dead. Alice Hamilton was determined to prevent such a tragedy from happening again. By the time of the accident, Hamilton had pioneered the field of industrial medicine in the United States. She specialized in workplace safety years before the Occupational Safety and Health Administration was created. She was the first female professor at Harvard. She spent decades inspecting factories and mines. But this time, she was up against a formidable new foe: America's relentless push for progress, regardless of the cost. The 1920s were an exciting decade. Industry was booming. Labor was flourishing. Automobiles were changing roads, cities, and nearly all parts of American life. And one day, an ambitious scientist named Thomas Midgley Jr. triumphantly found just the right chemical to ensure that this boom would continue. His discovery-tetraethyl leaded gasoline-set him up for great wealth and the sort of fame that would land his name in history books. Soon, Hamilton would be on a collision course with Midgley, fighting full force against his invention, which poisoned the air we breathe, the water we drink, and the basic structure of our brains. American Poison is the gripping story of Hamilton's unsung battle for a healthy planet-and the ramifications that continue to echo today"--
Includes bibliographical references and index.
Keywords: Hamilton, Alice, -- 1869-1970.; Midgley, Thomas, -- Jr., -- 1889-1944.; Tetraethyllead -- Toxicology; Gasoline -- Anti-knock and anti-knock mixtures -- History; Industrial toxicology -- United States -- History -- 20th century; Gasoline industry -- United States -- Safety measures; Toxicologists -- United States -- Biography; Medicine, Industrial -- United States -- History